Prediction of Self-Efficacy and Aggression in Adolescents Based on Marital Conflicts and Mothers’ Problem-Solving Styles - Golsorkhi , Mina; Jahanian , Saeed; Mahmoudimozafar , Majid (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate the predictive role of maternal marital conflict and mothers’ problem-solving styles on adolescent self-efficacy and aggression. Methods and Materials: The research employed a descriptive-correlational design and was conducted on a sample of 352 mother-adolescent daughter dyads selected through multi-stage cluster sampling from public secondary schools in District 5 of Tehran during the 2023–2024 academic year. Data were collected using the General Self-Efficacy Scale (GSE-17), the Buss-Perry Aggression Questionnaire (BPAQ), the Marital Conflict Questionnaire (MCQ-R), and the Problem-Solving Styles Inventory by Cassidy and Long. Descriptive statistics, Pearson correlation coefficients, and multiple regression analyses using the stepwise method were performed via SPSS version 27. Findings: The results showed that maternal marital conflict significantly predicted adolescent self-efficacy negatively (B = -0.205, β = -0.407, p < .001) and adolescent aggression positively (B = 0.202, β = 0.409, p < .001). Among maternal problem-solving styles, avoidance was the strongest positive predictor of aggression (B = 8.421, β = 0.602, p < .001) and a significant negative predictor of self-efficacy (B = -8.289, β = -0.580, p < .001). Conversely, control, creativity, confidence, and approach orientation in problem-solving positively predicted adolescent self-efficacy and negatively predicted aggression. Helplessness was also a significant negative predictor of self-efficacy and a positive predictor of aggression, though with smaller effect sizes. Conclusion: Maternal marital conflict and problem-solving styles significantly influence adolescents’ psychological outcomes. Constructive maternal problem-solving traits act as protective factors, enhancing self-efficacy and reducing aggression, whereas avoidant or helpless styles exacerbate negative outcomes.